PSYCHOSOCIAL SUPPORT IN INCREASING COVID-19 AND MENTAL HEALTH IN THE ELDERLY - Rizki Muliani; Tri Nur Jayanti; Inggrid Dirgahayu; Irfan Safarudin; Anri Anri (JCES (Journal of Character Education Society), 2021)
Abstrak: RW 01 Rancanumpang merupakan area komunitas dengan jumlah usia lansia (24,2%) terbanyak kedua setelah usia dewasa (41,8%). Posbindu sebagai tempat pelayanan kesehatan yang mudah dijangkau oleh lansia telah di non aktifkan sejak Maret 2020 sebagai upaya meminimalkan penyebaran COVID-19. Hal ini menyebabkan munculnya masalah psikososial bagi lansia karena tidak adanya akses untuk melakukan pemeriksaan kesehatan secara periodik. Oleh karena itu, kegiatan ini bertujuan untuk mengaktifkan kembali Posbindu dan memberikan dukungan psikososial agar dapat mengoptimalkan kesehatan lansia. Metode pelaksanaan kegiatan ini meliputi penyuluhan tentang Adaptasi Kebiasaan Baru (AKB); penjelasan dan simulasi pelaksanaan Posbindu menggunakan protokol pencegahan penularan COVID-19; dan demonstrasi teknik penanganan masalah psikososial. Kegiatan ini melibatkan lansia dan kader sebagai sasaran kegiatan dan tim EFT sebagai trainer dan fasilitator saat demonstrasi penanganan masalah psikososial. Hasil dari kegiatan ini yaitu terlaksananya rangkaian kegiatan yang dihadiri oleh para lansia dan kader sesuai dengan perencanaan, adanya peningkatan pengetahuan lansia tentang AKB, peningkatan kemampuan kader dalam melaksanakan Posbindu menggunakan protokol kesehatan, dan peningkatan kemampuan lansia untuk mempraktikkan Emotional Freedom Technique (EFT) dalam penanganan masalah psikososial serta penurunan masalah psikososial setelah diberikannya EFT pada lansia. Diharapkan kader dapat memberikan dukungan psikosial pada lansia sehingga lansia mampu beradaptasi dengan berbagai perubahan di era new normal.Abstract:  RW 01 Rancanumpang is a community area with the second-highest number of elderly (24.2%) after adulthood (41.8%). Posbindu as a place of health services that are easily accessible to the elderly has been deactivated since March 2020 as an effort to minimize the spread of COVID-19. This situation causes concern and the emergence of psychosocial problems for the elderly because they do not have access to periodic medical examinations. Therefore, the objective of implementing activities in the form of reactivating Posbindu and providing psychosocial support is expected to help optimize the health status of the elderly in RW 01 Rancanumpang. The implementation of this activity uses several methods, namely counseling on New Habit Adaptation (AKB); explanation and simulation of the implementation of Posbindu using a protocol for preventing transmission of COVID-19, and; demonstration of psychosocial problem management techniques in the elderly. This activity involves the elderly community and cadres as the target of the activity and the EFT team as trainers and facilitators during demonstrations of handling psychosocial problems. The result of this activity is the implementation of a series of activities attended by the elderly and cadres according to the plan. There is an increase in the knowledge of the elderly about IMR, an increase in the ability of cadres in implementing Posbindu using health protocols, and an increase in the ability of the elderly to practice Emotional Freedom Technique (EFT) in handling psychosocial problems and a decrease in psychosocial problems after EFT is given to the elderly. The conclusion is that there is an increase in the knowledge of the elderly after being given counseling on AKB, cadres can apply health protocols in the implementation of posbindu and the elderly experience a decrease in psychosocial problems after being given EFT. It is hoped that cadres can provide psychosocial support to the elderly so that the elderly can adapt to various changes in the new normal era.